2022
DOI: 10.2147/ijgm.s366925
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Approaches Identify Necroptosis‑Related Prognostic Signature and Associated Regulatory Axis in Cervical Cancer

Abstract: Background Cervical cancer is the fourth most frequent malignancy among women globally, with approximately 604,000 new cases and 341,000 deaths per year. Necroptosis is a newly discovered mechanism of cell death involved in biological behaviors of cancer. Methods LASSO Cox regression analysis was conducted to construct a prognostic necroptosis-related signature. lncRNA–miRNA–mRNA regulatory axis was constructed with a ceRNA network. qRT-PCR was performed to verify our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Therefore, the development of biomarkers that can predict the prognosis and treatment benefit of HNSCC patients is necessary. With the advancement of high-throughput sequencing technology and the development of bioinformatics, researchers have more deeply decoded HNSCC and derived a large number of biomarkers ( Zhan et al, 2022 ; Zhang et al, 2022 ). These biomarkers covered a wide range of biological functions, including inflammation, pyroptosis, immunity, and hypoxia et al ( Han et al, 2022 ; Li et al, 2022 ; Lu and Jia, 2022 ; Zhu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the development of biomarkers that can predict the prognosis and treatment benefit of HNSCC patients is necessary. With the advancement of high-throughput sequencing technology and the development of bioinformatics, researchers have more deeply decoded HNSCC and derived a large number of biomarkers ( Zhan et al, 2022 ; Zhang et al, 2022 ). These biomarkers covered a wide range of biological functions, including inflammation, pyroptosis, immunity, and hypoxia et al ( Han et al, 2022 ; Li et al, 2022 ; Lu and Jia, 2022 ; Zhu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the researchers found that necroptosis inhibited tumor progression and metastasis by regulating programmed tumor cell death in various solid tumors ( Beretta and Zaffaroni, 2022 ). Necroptosis has been used as a novel biomarker to guide the treatment of cancer patients in clinical practice ( Chen et al, 2022 ; Luo et al, 2022 ; Zhan et al, 2022 ). For example, Luo et al have precisely predicted the prognosis and treatment benefit of colorectal cancer patients by developing necrosis-related molecular characteristics ( Chen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…GLUD1 and PYGL have been shown to be activated downstream of RIPK3 in necroptosis. 98 Other groups have also used similar transcriptomics and bioinformatic approaches to establish a necroptosis-related prognostic model in different types of cancers, such as cervical cancer, 99 renal carcinoma, 100 pancreatic adenocarcinoma 101 and other cancers where regulation of necroptosis-related genes affects tumorigenesis. 102 In addition to cancer, a transcriptomic and metabolic profiling study showed the involvement of necroptosis in chronic obstructive pulmonary disease (COPD).…”
Section: Implications and Opportunities For Diagnostics And Therapeut...mentioning
confidence: 99%
“…The most prevalent cancer among women worldwide is cervical cancer, and according to statistics, approximately 527,624 new cases of cervical cancer are diagnosed each year 1–3 . Chemotherapy is currently the primary treatment for cervical cancer.…”
Section: Introductionmentioning
confidence: 99%